Biomass production of sun-mushroom and shiitake in liquid culture media with agroindustrial residues - Lopes, Aline (Boletim Centro de Pesquisa de Processamento de Alimentos, 2020)
The objective of this work was to evaluate economically feasible liquid culture media for the production of fungal biomass and to promote recycling of agro-industrial wastes. It was verified if the amount of biomass produced was sufficient to substitute synthetic culture media and constitute inoculum for matrices production, therefore improving the technology and reducing the costs of culture processing. The inoculation Lentinula edodes and Agaricus blazei isolates was performed in liquid culture, media constituted by decocts of the residual substrate of Pleurotus spp. culture and residue of stevia leaves, employing as controls PD media (potato-dextrose) and mineral media, respectively. The liquid culture media from residual substrate of Pleurotus spp. showed the best behavior in the production of mycelial biomass of L. edodes and similar performance to the traditional mineral media for A. blazei. Therefore, the media consisted of Pleurotus spp. culture residue is a viable alternative for the production of mycelial biomass of both fungal species.